Access to Scientific Publication through GS Spark - Mishra, Anjay Kumar (GS Spark: Journal of Applied Academic Discourse, 2023)
The editorial highlighted GS Spark needs along with the issues of scientific publication and ways forward. It extended acknowledgments and short review of article published in editorial perspective along with good wishes. The push for open access publishing in the scientific community is aimed at making research more accessible to the public and promoting collaboration among researchers. However, many of the current efforts to increase access to scientific knowledge, such as increasing funds for subscription fees or article processing charges (APCs), may actually reinforce the dominance of a few publishing houses and maintain the existing market model. One of the main challenges in transitioning to open access publishing is the need to cover the costs that are currently supported by subscription fees. While some open access journals are funded by institutional subscribers or dedicated open-access publishers, many traditional publishers have also started offering open access options. However, these publishers may still benefit from the existing market structure and the lack of price sensitivity among researchers, potentially leading to a new pay-to-publish system that is more costly than the previous subscription model. This made us to initiate GS Spark: Journal of Applied Academic Discourse. We would also like to acknowledge the contributions of all the authors, reviewers, and readers who have supported GS Spark: Journal of Applied Academic Discourse. Thank you for your valuable time, effort, and expertise. I wish you all on behalf of journal team a happy and prosperous Dashain, Tihar and Chhath.